PENTINGNYA ASPEK GOVERMENT POWER DALAM PENGEMBANGAN INDUSTRI PARIWISATA DAERAH - Irany Windhyastiti; Diah Widiawati (University of Merdeka Malang, 2016)
The tourism industryhas the characteristicinterdependence : (1)Hospitality Industry(Food andBaverage,and accommodation);(2)Travel (Retail andWholeseller;The operator);(3) VisitorServices (Attraction;Event;andTourismAgencies).Therefore,to builda strongtourism industryneededa strongorganisationalrelationships.Powerand dependence isan importantbasicbuildingcooperation betweenorganizations. One of thecities inIndonesiathat are prominentintourismisKota Batu. Kota Batu is theicon oftourism in East Java.Even in the year 2006-2007, the industry of tourism in Kota Batu had dropped shraply because of overflow of Lapindo mud. In 2012, the total tourists visiting the Kota Batu reached 1,603,441 visitors. In 2013 increased 1,881,446 and 2,089,022 tourists in 2014. That number rises quickly compared in 2007, when the condition of the Kota Batu dropped as the number of tourist visits less than 1 million people.Now, in2016,The government of Kota Batu targetrevenueof Rp1trillion,where80%is derived fromthe tourism sector. Therefore, in the study will be analized how the government power in developing the tourism industry in Kota Batu. The technical analysis of this research uses a combination of analysis statistics and policy analysis.The analysis unit of this studyis thetourism industryin Kota Batu.This research populationare thestakeholders inthe tourism industry: tourism entrepreneur and community. Based on the statistics analysis, the aspect of power has significant influence towards the development of the tourism industry. This shows the importance of the government role in developing the tourism industry.